Design and Analysis of Metasurface Antenna for Beam Steering Applications - Sirisha N; Rohith M; Vamsi M; Vinod Kumar M (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper presents a novel beam-steering approach utilizing a single microstrip patch antenna operating at 12.5 GHz in conjunction with a metallic metasurface reflector. The primary goal is to enhance either the bandwidth or gain while enabling effective beam steering across various angles. In contrast to conventional horn antennas, our proposed design offers a more compact and potentially more efficient configuration, making it well-suited for contemporary wireless communication and radar systems. The metallic metasurface reflector is specifically engineered to dynamically manipulate the reflected wavefront, allowing for controlled beam steering without the need for intricate phase-shifting networks. The design process involves comprehensive electromagnetic simulations to optimize the antenna’s performance, with a focus on critical parameters such as gain, bandwidth, radiation pattern, and impedance matching. The target bandwidth for the proposed design is 700 MHz, aiming to provide improved frequency coverage. The final prototype will undergo experimental validation to ascertain its real-world efficacy. Through this research, we endeavor to develop an innovative, high-performance beam-steering system that delivers enhanced efficiency and adaptability in dynamic wireless environments.